Sistem Informasi Pemesanan Obat Secara Online Pada PT. Mefrofam - Anastasia Kembaren (Journal of Information System Research (JOSH), 2019)
Drug Order Information System was created to convey information about PT. Meprofarm to the wider community through the internet which so far is still using information books, as well as ordering drugs at PT. Meprofarm which still uses computerized ordering using Microsoft Word and Microsoft Excel. Can make it easier for customers in the process of ordering drugs. The purpose of this study was to develop a drug ordering information system at PT. Meprofarm easily and efficiently. Data collection methods used in the preparation of this Final Project are Observation, Library Studies, and Interviews. This program was developed using Macromedia Dreamweaver MX 2004 using the Php Triad database. With this proposed system, the company can obtain information on ordering goods quickly and accurately. In addition, drug order reports can be printed as needed efficiently and effectively. Online Drug Ordering at PT. Meprofarm is made by writers who are ready to be developed.